In Vitro Susceptibilities of Worldwide Isolates of Intrapulmonary Aspergillus Species and Important Candida Species in Sterile Body Sites against Important Antifungals: Data from the Antimicrobial Testing Leadership and Surveillance Program, 2017–2020 - Shio-Shin Jean; Hung-Jen Yang; Po-Chuen Hsieh; Yu-Tsung Huang; Wen-Chien Ko; Po-Ren Hsueh (Microbiology Spectrum, 2022)
ABSTRACT To understand the changes of resistance in clinically commonly encountered fungi, we used the Antimicrobial Testing Leadership and Surveillance (ATLAS) database to explore in vitro antifungal susceptibilities against clinically important isolates of Aspergillus and Candida species (collected from intrapulmonary and sterile body areas, respectively). We applied the CLSI antifungal 2020 and the EUCAST antifungal 2020 guidelines. From 2017 to 2020, isolates of intrapulmonary Aspergillus fumigatus (n = 660), Aspergillus niger (n = 107), Aspergillus flavus (n = 96), Aspergillus terreus (n = 40), and Aspergillus nidulans species complex (n = 26) and sterile site-originated isolates of Candida albicans (n = 1,810), Candida glabrata (n = 894), Candida krusei (n = 120), Candida dubliniensis (n = 107), Candida lusitaniae (n = 82), Candida guilliermondii (n = 28), and Candida auris (n = 7) were enrolled in this study. Using the EUCAST 2020 breakpoints, it was demonstrated that amphotericin B and posaconazole displayed poor in vitro susceptibility rates against A. fumigatus isolates (<50% and 18.9%, respectively). In contrast, isavuconazole and itraconazole showed high in vitro potency against most Aspergillus isolates (>92%). Most intrapulmonary Aspergillus isolates exhibited MICs of ≤0.06 μg/mL to anidulafungin. Furthermore, intrapulmonary A. fumigatus isolates collected from Italy and the United Kingdom exhibited lower in vitro susceptibility to isavuconazole (72.2% and 69%, respectively) than those in the remaining ATLAS participant countries (>85%). Higher isavuconazole MIC90s against C. auris and C. guilliermondii (1 and 4 μg/mL, respectively) were observed compared to the other five Candida species. Despite the aforementioned MICs and susceptibilities against fungi, research needs to consider the pharmacokinetic (PK) profiles, pharmacodynamic (PD) parameters, and clinical treatment experience with antifungals against specific Aspergillus species. IMPORTANCE In addition to monitoring the antifungal susceptibilities of clinically important fungi, reviewing the PK/PD indices and the clinical therapy experience of antifungals under evaluation are important to guide an appropriate antifungal prescription. The efficacies of liposomal amphotericin B complex and anidulafungin for the treatment of pulmonary aspergillosis caused by different Aspergillus species need to be periodically evaluated in the future.